Trdnostna analiza rotorja ventilatorja borbenega vozila - Kunc, Robert (Strojniški vestnik, 1999)
Because of the deficiencies with an existing combat vehicle fan, we decided to design a new fun rotor with improved aerodynamic and strength properties. The new rotor should assure a sufficient mass flow of the cooling air through the motor cooling system during full power operation under the most unfavourable operating conditions (desert heat). The rotor strength must be compatible with the operating conditions such as high rotational speed, off road driving and shooting. This article describes the rotor model with improved aerodynamic properties, which has been checked on a dedicated test stand. We have measured the fun response to external excitation as a function of the rotational speed. The stress and strain conditions in the rotor have been checked using FEM.
Keywords: vozila borbena; rotorji ventilatorjev; analize trdnostne; modeliranje rotorjev; vojaška vozila; rotorji; ventilatorji; modeliranje; mehanske lastnosti